Highlight on lipids and its use for covalent and non-covalent conjugations - Abdullah Q. Khudhur; Nidhal K. Maraie; Ayad M.R. Raauf (College of Pharmacy / Mustansiriyah University, 2020)
Lipids are organic fatty or waxy compounds which are used to make nanocarriers that are promising for drug delivery. When lipids associated covalently (lipid-drug conjugate LDC) or non- covalently (drug-lipid complex) to drugs to form Lipid Drug Conjugates (LDC). Most common types of lipids   used for drug conjugation are fatty acids, glycerides, steroids, and phospholipids. Conjugation with lipids may change the properties of the drug and significantly increase the drug lipophilicity. Lipid-drug conjugation could improve the delivery of drugs by the lymphatic system, enhance bioavailability of oral administered drugs, improve drug targeting in tumor diseases, enhance the loading of drugs into some delivery carriers, increase drug stability, and many others. Lipid-drug conjugates can be prepared through different strategies for conjugation and by chemical linkers depending on the chemical structure of both drugs and lipids, careful selection of lipids and drug are necessary in designing the lipid-drug conjugate to achieve maximum benefits.